Why doctors consider leaving UK medicine: qualitative analysis of comments from questionnaire surveys three years after graduation - Lambert, T; Smith, F; Goldacre, M (SAGE Publications, 2017)
Objective: To report the reasons why doctors are considering leaving medicine or the United Kingdom (UK). Design: Questionnaire survey. Setting: UK. Participants: Questionnaires were sent three years after graduation to all UK medical graduates of 2008 and 2012. Main outcome measures: Comments from doctors about their main reasons for considering leaving medicine or the UK (or both). Results: The response rate was 46.2% (5291/11461). 60% of respondents were not definitely intent on remaining in UK medicine: 50% were considering working in medicine outside the UK and 10% were considering leaving medicine. Among those considering working in medicine outside the UK, the most commonly cited reasons were to gain wider experience, that things would be ‘better’ elsewhere, and a negative view of the NHS and its culture, state, and politics. Other reasons included better training or job opportunities, better pay and conditions, family reasons, and higher expectations. Three years after graduation, doctors surveyed in 2015 were significantly more likely than doctors surveyed in 2011 to cite factors related to the NHS, to pay and conditions, to their expectations, and to effects on work-life balance and patient care. Among those considering leaving medicine, the dominant reason for leaving medicine was a negative view of the NHS (mentioned by half of those in this group who commented). Three years after graduation, doctors surveyed in 2015 were more likely than doctors surveyed in 2011 to cite this reason, as well as excessive hours and workload, and financial reasons. Conclusions: An increasingly negative view is held by many doctors of many aspects of the experience of being a junior doctor in the NHS, and the difficulty of delivering high quality patient care within what many see as an under-funded system. Policy changes designed to encourage more doctors to remain should be motivated by a desire to address these concerns by introducing real improvements to resources, staffing and working conditions.